2011
DOI: 10.1148/radiol.10101008
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Carotid Artery Atherosclerotic Lesion Echogenicity and Severity at Standard US with Intraplaque Neovascularization Detected at Contrast-enhanced US

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.10101008/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
3
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 45 publications
5
103
3
11
Order By: Relevance
“…Pseudoenhancement occurred in the far wall adventitia of the carotid artery; vascularization within intima-media complex was prevalently evaluated at the near wall. The degree of intima-media neovascularization at CEUS was categorized according to Staub et al (9,14) as follows: grade 0 5 no vascularization, indicating no appearance of microbubble contrast agent in the media-intima layer; grade 1 5 limited or moderate vascularization, indicating limited to moderate visible appearance of moving microbubbles in the intimamedia layer; or grade 2 5 severe vascularization, indicating extensive vascularization of the intima-media layer with clear visible appearance of microbubbles ( Figure 1). If there was a discrepancy in the scores of the 2 independent readers (GG and PM), a consensus was reached.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudoenhancement occurred in the far wall adventitia of the carotid artery; vascularization within intima-media complex was prevalently evaluated at the near wall. The degree of intima-media neovascularization at CEUS was categorized according to Staub et al (9,14) as follows: grade 0 5 no vascularization, indicating no appearance of microbubble contrast agent in the media-intima layer; grade 1 5 limited or moderate vascularization, indicating limited to moderate visible appearance of moving microbubbles in the intimamedia layer; or grade 2 5 severe vascularization, indicating extensive vascularization of the intima-media layer with clear visible appearance of microbubbles ( Figure 1). If there was a discrepancy in the scores of the 2 independent readers (GG and PM), a consensus was reached.…”
Section: Methodsmentioning
confidence: 99%
“…This technique was also used for identifying and quantifying carotid artery vasa vasorum and intraplaque neovascularization in patients with atherosclerotic carotid artery lesions (10)(11)(12). A correlation was found between the inflammation observed on histopathologic analysis of the plaque after endarterectomy and the degree of intraplaque neovascularization on CEUS (13)(14)(15). The aim of this study was to assess the findings of carotid artery CEUS in a series of consecutive LVV patients with different degrees of disease activity and to compare CEUS with PET findings.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the technique allows direct visualization of the adventitial vasa vasorum and intraplaque angiogenesis. A recent article by Staub et al [89] concluded that vulnerable plaques frequently have a greater degree of neovascularization and that the presence of plaque neovessels correlates with lesion severity and with morphologic features of plaque instability. Therefore, contrast-enhanced ultrasound can represent a valuable tool for risk stratification of unstable plaques [89].…”
Section: Contrast Enhancement (Us-mri-ct)mentioning
confidence: 99%
“…Homogeneous echo plaques were defined as plaques with an echogenicity less than that of the surrounding adventitia for >80% of the plaque area, without acoustic shadowing. Mixed plaques were defined as plaques containing <90% of the circumferential calcification or with associated echo-dense and anechoic regions that occupied <80% of the plaque area (24). Homogeneous echo plaques were named as 1 and mixed as 2.…”
Section: Methodsmentioning
confidence: 99%